ANALISIS PENYELENGGARAAN PROGRAM PARENTING DI TK MAMAMPANG KABUPATEN BULUKUMBA - sarmiani, sarmiani; badaruddin, muhaemin; Latif, M. Ali (UNIVERSITAS NEGERI MAKASSAR, 2025)
This research examines the analysis of the implementation of parenting programs at TK Mamampang Bulukumba Recency. The research subjects include 4 individuals, comprising 1 school principal, 1 teacher/staff, and 2 parents of strudent. Data was collected through obsevation, interviews, and documentation. The data weree processed using procedures for data reduction, data presentation, conclusion drawing, and verification. The results indicate that supportive factors for the implementation of the parenting program include high community support, collaboration between institutions, and the availability of adequate resources. Menawhile, inhibiting factors involve financial constraints, low community participation, and challenges in technology. This highlights the need for a holistic approach and balance between schools and families. Through dialogue and discussion, theses meetings aim to understand student development, share information, and create an environment that supports the optimal growth of children.